DYNAMIC RESTORATION OF PROFILES ACROSS DIAPIRIC SALT STRUCTURES: NUMERICAL APPROACH AND ITS APPLICATIONS - Ismail-Zadeh A.T.; Talbot C.J.; Volozh Y.A. (My University, 2001)
The backstripping method that is widely used in basin analysis sometimes fails for salt-bearing basins because the highly mobile and buoyant salt deforms its sedimentary overburden. We present a numerical approach for 2-D dynamic restoration of cross-sections through successive earlier depositional stages. The approach is based on a solution of the inverse problem of the gravitational (Rayleigh±Taylor) instability and combines the Galerkin-spline ®nite-element method with interface tracking and a backstripping method. Our model interprets basin pro®les as multiple layers of viscous ¯uids with various densities and viscosities. The evolution of salt structures is modelled backward in time by removing successively younger layers and restoring older layers and any diapirs to the stage they were likely to have been. We test the sensitivity of the restoration technique to small variations in density of the layers at different stages in the evolution of diapiric structures. The applicability of the technique was demonstrated by reconstructions of upbuilt and downbuilt diapirs. The technique is used to restore a depth-converted seismic cross-section through the southeastern part of the Pricaspian salt basin. Mature salt diapirs in the section are shown to have been downbuilt from a salt layer with an initially uniform thickness as a result of differential sedimentary loading until the end of the Triassic before one of the diapirs was buried and actively upbuilt. The numerical approach is well suited for restoration of cross-sections with ductile overburdens, but despite limitations can be developed to 3-D restorations and other rheologies.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая